Dental implants - Quo vadis? - Levin, Liran; Schwartz-Arad, Devorah (Journal of Osseointegration, 2010)
The use of osseointegrated implants as a foundation for prosthetic replacement of missing teeth has become widespread over the past several decades. Implant therapy is a common, almost daily practice, and will probably gain in popularity during the next several years. In the near future of implant dentistry, there will be a need for further research to prevent and treat implant failure and complications in order to improve the long-term implant success and eliminate implant-related complications. The goal of our cumulative knowledge from dental implant research is to provide the patient with immediate tooth replacement in the simplest, quickest and most functionally and esthetically predictable way.